2022
DOI: 10.1007/s00066-022-01953-y
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score-matched analysis comparing dose-escalated intensity-modulated radiation therapy versus external beam radiation therapy plus high-dose-rate brachytherapy for localized prostate cancer

Abstract: Purpose Dose-escalated external beam radiation therapy (EBRT) and EBRT + high-dose-rate brachytherapy (HDR-BT) boost are guideline-recommended treatment options for localized prostate cancer. The purpose of this study was to compare long-term outcome and toxicity of dose-escalated EBRT versus EBRT + HDR-BT boost. Methods From 2002 to 2019, 744 consecutive patients received either EBRT or EBRT + HDR-BT boost, of whom 516 patients were propensity score match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In their retrospective study, Kishan et al also found improvements in disease-specific survival when comparing BTB with ADT and EBRT with ADT, but many patients with EBRT and ADT received insufficient K EBRT doses [23]. A propensity score-matched analysis by Tamiharda et al showed no significant difference between EBRT and BTB, although many patients did not receive ADT or pelvic irradiation in that study, and the BTB dose was only 100 Gy EQD2Gy [24]. In considering toxicity, most [7,25] but not all [2] studies showed increased toxicity with BTB.…”
Section: Discussionmentioning
confidence: 96%
“…In their retrospective study, Kishan et al also found improvements in disease-specific survival when comparing BTB with ADT and EBRT with ADT, but many patients with EBRT and ADT received insufficient K EBRT doses [23]. A propensity score-matched analysis by Tamiharda et al showed no significant difference between EBRT and BTB, although many patients did not receive ADT or pelvic irradiation in that study, and the BTB dose was only 100 Gy EQD2Gy [24]. In considering toxicity, most [7,25] but not all [2] studies showed increased toxicity with BTB.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, BT with hormonotherapy increases the progression-free survival rates for men with localized prostate cancer [47]; however, the study did not evaluate GU toxicity. In one study evaluating EBRT for men with localized prostate cancer, HT increased the risk of grade 2 acute GU toxicities significantly [48,49]. A meta-analysis reported that HT combined with RT could decrease micro-metastases and delay biochemical relapse; however, both RT and HT S368 X. Li et al / Comparison of chronic GI and GU toxicities between BT and external beam RT have a greater toxicity than RP [50].…”
Section: Discussionmentioning
confidence: 99%
“…Dose-escalated external beam radiation therapy (EBRT) and EBRT plus high-dose rate brachytherapy (HDR-BT) are well-established recommended treatment options for localized PC [141]. It was discovered that circRNAs can improve the effectiveness of radiation therapy in PC through miR-141-3p sponging and the regulation of TR4/QKI/circZEB1/miR-141-3p/ZEB1 axis [100].…”
Section: Prostate Cancermentioning
confidence: 99%